A Community Based Study of Depression and Its Risk Factors among Geriatric Population Inperiurban Areas of Tamilnadu - Devi Kittu; Logesh Wari (Medsci Publications, 2017)
Background: Geriatric depression is an important public health problem. There is a dearth of community studies from India investigating geriatric depression and its associated risk factors. This study aimed to establish the prevalence and factors associated with geriatric depression in asemiurbanpopulation of Melmaruvathur. Methods: This was a community based cross sectional study conducted in semiurban areas of Melmaruvathur. 200 individuals in the geriatric age group were randomly selectedand were interviewedusing standard Geriatric depression scale and the result wasanalyzed using the statistical software SPSS 20. Results: Prevalence of geriatric depression was 65% with 14.5% mild and 50.5% with severe depression. Depression was significantly associated with elders in the age group of 60-69 years. The proportion of severe depression was significantly higher among those participants whose spouse had expired (85.56% vs 14.44%). The proportion of depression was significantly higher among the elders who gave a previous history (92.13%) of depression. The proportion of elders who require home care was also significantly associated with depression. Conclusions: Geriatric depression is highly prevalent in thesemiurbanareas of Melmaruvathur. Age, status of spouse, previous history of depression, elders whorequires home care was the significant factors that was associated with depression in geriatric population.